Screening for the Presence of Salmonella typhimurium in Local Meat using Dot-Elisa (Journal of Environmental Microbiology and Toxicology, 2014)
Salmonella infections in commercial poultry have long been an industry concern and the subject of many investigations. Since poultry is a major food source, its contamination with salmonellae may result in the development of human illness. Salmonella typhimurium is one of paratyphoid Salmonellae most commonly associated with poultry. Thus, a detection assay for this bacterium is highly sought after. Detection of Salmonella typhimurium using monoclonal antibody is specific to only one epitope while polyclonal antibody has the ability to detect various serovars due to the presence of multitude of epitopes. In this study the production of polyclonal antibody was performed using rabbits immunized with formalin-killed cell lysate of Salmonella enterica subsp. enterica serovar typhimurium ATTCÂ® 53648. The purification of immunoglobulin G (IgG) was carried out by affinity chromatography and the purity of IgG was characterized by SDS-PAGE.The purified IgG was used to detect Salmonella typhimurium by the dot-ELISA method. The specificity of the dot-ELISA was investigated with different foodborne pathogens including Escherichia coli O157:H7 and Campylobactor jejuni which produced no significant reaction signal compared to Salmonella typhimurium.
Keywords: Salmonella; Poultry; PAb; Dot Blot